Communication, Coordination, and Security for People with Multiple Sclerosis (COCOS-MS): a randomised phase II clinical trial protocol. Issue 1 (25th January 2022) - Golla, Heidrun; Dillen, Kim; Hellmich, Martin; Dojan, Thomas; Ungeheuer, Solveig; Schmalz, Petra; Staß, Angelika; Mildenberger, Vanessa; Goereci, Yasemin; Dunkl, Veronika; Strupp, Julia; Fink, Gereon R; et al.
Abstract : Introduction: Patients with multiple sclerosis (MS) have complex needs that range from organising one's everyday life to measures of disease-specific therapy monitoring to palliative care. Patients with MS are likely to depend on multiple healthcare providers and various authorities, which are often difficult to coordinate. Thus, they will probably benefit from comprehensive cross-sectoral coordination of services provided by care and case management (CCM). Though studies have shown that case management improves quality of life (QoL), functional status and reduces service use, such benefits have not yet been investigated in severely affected patients with MS. In this explorative phase ll clinical trial, we evaluated a CCM with long-term, cross-sectoral and outreaching services and, in addition, considered the unit of care (patients and caregivers). Methods and analysis: Eighty patients with MS and their caregivers will be randomly assigned to either the control (standard care) or the intervention group (standard care plus CCM (for 12 months)). Regular data assessments will be done at baseline and then at 3-month intervals. As primary outcome, we will evaluate patients' QoL. Secondary outcomes are patients' treatment-related risk perception, palliative care needs, anxiety/depression, use of healthcare services, caregivers' burden and QoL, meeting patients' and caregivers' needs, and evaluating the CCM intervention. We will also evaluate CCM through individual interviews and focus groups. The sample size calculation is based on a standardised effect of 0.5, and one baseline and four follow-up assessments (with correlation 0.5). Linear mixed models for repeated measures will be applied to analyse changes in quantitative outcomes over time. Multiple imputation approaches are taken to assess the robustness of the results. The explorative approach (phase ll clinical trial) with embedded qualitative research will allow for the development of a final design for a confirmative phase lll trial. Ethics and dissemination: The trial will be conducted under the Declaration of Helsinki and has been approved by the Ethics Commission of Cologne University's Faculty of Medicine. Trial results will be published in an open-access scientific journal and presented at conferences. Trial registration number: German Register for Clinical Studies (DRKS) (DRKS00022771).